Frequency of Parasymphysis Fracture in Mandibular Fractures Due to Road Traffic Accidents - Marjan Noor, Raheel Hassan, Abid Hussain Bukhari, Rashida Hilal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of parasymphysis fracture in mandibular fractures due to road traffic accidents. Study Type: Cross-sectional study Duration and Place of Study: Department of OMF Surgery Ayub Teaching Hospital, Abbottabad from 1st December 2019 to 30thMay 2020 Methodology: One hundred and forty eight patients were shifted to the Radiology Department for X-rays of mandible . Fractures of mandible especially fracture of parasymphysis were seen. Results: The mean age was 47.46±21.25 years. Fractured parasymphysis was found in 75 (82%) male patients and female patients were 14% (8/57). Conclusions: The gender was found to be significantly associated with the outcome i.e. parasymphysis fracture in mandibular fractures due to road traffic accidents. The age, number of fractures and type of fractures were not found to be significantly associated with the outcome i.e. parasymphysis fracture in mandibular fractures due to road traffic accidents. Keywords: Parasymphysis fracture, Mandibular fractures, Facial injury